M25 Weight loss has a significant impact on anti-fibrotic drug tolerance in patients with idiopathic pulmonary fibrosis. (15th November 2017) - Moon, RDC; Barker, E; Agnew, S; Sutcliffe, J; Kwok, A; Spencer, LG
Abstract : Introduction and Objectives: Nintedanib and pirfenidone are licensed anti-fibrotic therapies (AFT) for the treatment of Idiopathic Pulmonary Fibrosis (IPF). 1 Drug discontinuation rates in clinical trials were significant due to many side effects including weight loss. We aimed to establish average weight loss at 12 months in a group of patients commenced on AFT. Methods: This was a retrospective cohort study from a single tertiary ILD centre. All patients commenced on AFT for IPF between 1 st October 2014 and 31 st December 2015 were identified. Patients were assessed at 12 months for adherence to treatment and weight loss. Statistical analysis was conducted using GraphPad software. Results: 137 patients commenced anti-fibrotic medication during the study period (87 Nintedanib, 50 Pirfenidone). At 12 months 84/137 patients (61%) remained on therapy or died tolerating therapy [tolerant cohort]. 53/137 patients (39%) either died off therapy or failed to complete 12 months therapy [intolerant cohort], citing side effect burden or disease progression as a reason for treatment discontinuation. 14 patients within this intolerant cohort (25%) reported weight loss as a principal reason for treatment discontinuation [intolerant weight loss cohort]. At initiation of therapy, mean weight and BMI did not differ significantly between the tolerant and intolerant cohorts (tolerant vs intolerant; weight 81.8 kg vs 77.3 kg, p=0.13; BMI 29.1 vs 28.2, p=0.33). At 12 months, mean weight and BMI differed significantly between groups (weight 79.5 kg vs 68.7 kg, p=0.02; BMI: 28.2 vs 25.2, p=0.03). Within the intolerant weight loss cohort mean weight change at 12 months compared to the tolerant cohort was 8.9 kg vs 4.0 kg (p=0.004). The intolerant cohort was significantly older than the tolerant cohort (p=0.0003). Conclusions: Our data shows that patients intolerant of anti-fibrotic therapy are more likely to be older and to lose more weight during the course of treatment. BMI at the start of treatment was not predictive of drug discontinuation. Identification of progressive weight loss is important in order to implement strategies to improve overall drug tolerance. Reference: . NICE guidelines. Idiopathic pulmonary fibrosis in adults: Diagnosis and management. CG163 May, 2017.